2013
DOI: 10.1186/1758-5996-5-42
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic syndrome and sexual dysfunction among men with clinically diagnosed diabetes

Abstract: BackgroundThe worldwide epidemic of diabetes and obesity has resulted in a rapid upsurge in the prevalence of metabolic syndrome (MetS). MetS makes the individual liable to endothelial dysfunction which can initiate sexual dysfunction (SD). This study assessed the association between MetS and SD among clinically diagnosed diabetic subjects in Tema, Greater Accra Region of Ghana.MethodSexual functioning was assessed using Golombok Rust Inventory of Sexual Satisfaction in 300 consecutive diabetic men visiting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Five of the studies included in this review were from Nigeria [46] , [47] , [48] , [49] , [50] , four from Ethiopia [51] , [52] , [53] , [54] , three from Ghana [32] , [55] , [56] , one each from South Africa [57] , Egypt [31] , Kenya [58] , Zimbabwe [59] , and Tanzania [60] . Concerning the sampling technique 12 of the studies [31] , [32] , [46] , [47] , [48] , [49] , [50] , [54] , [55] , [56] , [58] , [59] used consecutive sampling to select study participants. However, one study [60] did not report the sampling method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five of the studies included in this review were from Nigeria [46] , [47] , [48] , [49] , [50] , four from Ethiopia [51] , [52] , [53] , [54] , three from Ghana [32] , [55] , [56] , one each from South Africa [57] , Egypt [31] , Kenya [58] , Zimbabwe [59] , and Tanzania [60] . Concerning the sampling technique 12 of the studies [31] , [32] , [46] , [47] , [48] , [49] , [50] , [54] , [55] , [56] , [58] , [59] used consecutive sampling to select study participants. However, one study [60] did not report the sampling method.…”
Section: Resultsmentioning
confidence: 99%
“…These consisted of 11 studies used the International Index of Erectile Function tool [31] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [58] , [59] , [60] . Two of the studies used the Golombok Rust Inventory of Sexual Satisfaction criteria [32] , [55] . Only one study used the Sexual Health Inventory for Men items [57] and the remaining one [51] used changes in Sexual Functioning Questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with earlier reports indicating that metabolic syndrome is a common phenomenon among the Ghanaian type 2 diabetes mellitus population. The prevalence of metabolic syndrome among people with type 2 diabetes in the Ghanaian population ranged within 43.3% NCEP-ATP III [ 19 ], 43.4% NCEP-ATP III, and 51.8% IDF [ 18 ] and 55.9% NCEP-ATP III [ 1 ], 58% NCEP-ATP III [ 13 ], and 78.8% WHO [ 18 ]. Similar reports in other jurisdictions of high prevalence rates of metabolic syndrome (63.6%, 51%, and 56%) have been recorded among people with type 2 diabetes, respectively, in North-Central Nigeria and Saudi Arabia [ 30 – 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also noticed the prevalence of FSD for each domain increased with age (4). Previously studies indicated that sexual dysfunction had direct relationship with MetS in men (5). However there are limited data about this relationship in women in literature.…”
Section: Introductionmentioning
confidence: 94%